2017
DOI: 10.1186/s41239-017-0064-z
|View full text |Cite
|
Sign up to set email alerts
|

The acceptance and use of a virtual learning environment in higher education: an empirical study in Turkey, and the UK

Abstract: This study evaluated the acceptance and use of a virtual learning environment in higher education by using the unified theory of acceptance and use of technology (UTAUT) model. Study data were collected by means of a questionnaire form, completed by 1032 students receiving undergraduate education in Turkey and the United Kingdom, who currently use similar virtual learning environments. The role of performance expectancy, effort expectancy, social influence and facilitating conditions were evaluated and tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Thus, the usage of Moodle by the student was affected by facilitating conditions such as access to devices, lack of support, low efficacy, high data costs, lecturer feedback, among others. The results are consistent with several studies such as Abu-Al-Aish and Love (2013); Kurt and Tingöy (2017); Nistor et al (2014); Magsamen-Conrad et al (2015); Tan (2013), Attuquayefio and Addo (2014) who found out that performance expectancy and facilitating conditions were significant determinants. Access to appropriate devices that can facilitate effective learning by students in developing countries is a challenge.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the usage of Moodle by the student was affected by facilitating conditions such as access to devices, lack of support, low efficacy, high data costs, lecturer feedback, among others. The results are consistent with several studies such as Abu-Al-Aish and Love (2013); Kurt and Tingöy (2017); Nistor et al (2014); Magsamen-Conrad et al (2015); Tan (2013), Attuquayefio and Addo (2014) who found out that performance expectancy and facilitating conditions were significant determinants. Access to appropriate devices that can facilitate effective learning by students in developing countries is a challenge.…”
Section: Discussionsupporting
confidence: 92%
“…The moderating variables (Age, Gender, Voluntariness, and Experience) were not used in this study as the researcher felt that the constructs did not influence the usage of Moodle by university students. Several scholars researching technology acceptance by students made similar assumptions, such asRaman et al (2014);Liebenberg et al (2018);Attuquayefio and Addo (2014);Kurt and Tingöy (2017);Nistor et al (2014);Magsamen-Conrad et al (2015), andTan (2013), who investigated the adoption of various technologies by students.…”
mentioning
confidence: 99%
“…Systematic Literature Review is considered by researchers as a term adopted to refer to a particular research or research methodology [22]. Its development is carried out in gathering and evaluating related research on a particular topic focus [23], [24].…”
Section: Methodsmentioning
confidence: 99%
“…The findings show that actions, social impact and CCC substantially influence the Cloud classroom adoption. In their field of research, Kurt and Tingöy (2017) aimed at investigating to what degree students accept and use virtual or online school learning environments. The findings show that behavioral intent of the performance expectancy variables is significantly affected.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%